ACCOUNTING AND AUDIT OF CONSTRUCTION MACHINERY IN UZBEKISTAN ITS CLASSIFICATION, CONDITION AND MOVEMENT - Kholmirzaevich, Kholikulov Ozod (The journal of contemporary issues in business and government, 2021)
This paper discusses the theoretical and practical aspects of construction machines, including their condition, movement, and a system of performance indicators, as well as auditing procedures. such as ideas and recommendations for how to improve their work's methods for expressing mathematical formulas. To improve the classification, category, condition, movement, and audit of construction machinery in building projects, proposals and recommendations have been established.Scientific developments on the structure of fixed assets in construction companies in the Republic of Uzbekistan, the types of construction machinery, the description of their work, their condition, movement and a system of indicators representing their activities are reflected.